Saving and loan business management strategy of Satu Hati Village-Owned Enterprises (BUMDes) - Nuak, Fransiskus Seran; Djani, William; Kase, Petrus Kase (Goodwood Publishing, 2020)
Purpose: The purpose of this study is to analyze saving and loan business management strategy in Satu Hati Village-Owned Enterprises (BUMDes) In Naimana Village, Central Malaka Sub-District, Malaka District. Research methodology: This research used a descriptive research method with a qualitative approach. This research used purposive sampling technique. Results: The results of this study found that communication and cooperation are not good enough, there are no binding rules, and recording and bookkeeping are not in accordance with the borrower's deposit. Limitations: This research only analyzes Management Strategies for Savings and Loans at Satu Hati Village-Owned Enterprises (BUMDes) in Naimana Village, Central Malaka Sub-District, Malaka Regency. Contribution: This research becomes information for the development of Satu Hati Village-Owned Enterprises (BUMDes) so that this BUMDes can continue to grow. Keywords: Environmental observation, Management strategy, Savings and loans business, Strategy formulation, Village-Owned Enterprises (BUMDes)